Selecting Innovative Approaches to Teaching English to Law Students Via Questionnaire Analysis - Balykina-Halanets, Liudmyla; Balykin, Ivan; Баликіна-Галанець, Людмила Ігорівна; Баликіна-Галанець, Людмила (Atlantis Press, 2021)
English in Ukraine is one of the integral parts of the training of future lawyers, but there is a problem in accordance with the knowledge of the language by graduates. To solve the problem, in 2018-2019 the authors conducted a survey at five universities of Ukraine (Ivano-Frankivsk Institute of Law of the NU “OLA”, National University of Ostroh Academy, «KROK» University, Cherkasy Bohdan Khmelnytsky National University, V. N. Karazin Kharkiv National University). The survey revealed students' expectations of learning English at university, their desire to improve their teaching, and the current level of language proficiency of undergraduate students. The results of the survey became the basis for the study. According to the results of the survey, the article summarizes and formulates recommendations for improving English language teaching methods for law students
Keywords: English for professional purposes; legal English; teaching English at the university